Advertisement Remove all ads

If Y = Aemx + Benx, Show that `(D^2y)/Dx^2 - (M+ N) (Dy)/Dx + Mny = 0` - Mathematics

If y = Aemx + Benx, show that `(d^2y)/dx^2  - (m+ n) (dy)/dx + mny = 0`

Advertisement Remove all ads

Solution

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 12 Maths
Chapter 5 Continuity and Differentiability
Q 14 | Page 184
Advertisement Remove all ads

Video TutorialsVIEW ALL [2]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×